Physical and chemical characterization of femur during and after body development period in male and female rats - Yilmaz, Sadik; Baygeldi, Saime Betul; Kanmaz, Yesim Aslan; Guzel, Baris Can; Yilmaz, Yucehan; Karan, Meryem; Guzel, Fuat (Wiley, 2023)
The aim of this study was to determine the physical and chemical characteristics of the bone structures during four developmental periods. Forty Wistar Albino rats (20 male and 20 female) were divided into four groups including prepubertal period (group I), period between adolescence and adulthood (group II) and later (young adult period as group III and old adult period as group IV). The bones were analysed by morphometric measurements, XRF (X-ray fluorescence) analysis for mineral levels and BET analysis (Brunaurer-Emmett-Teller) for surface area and porosity. In morphometric measurements, the GL (greatest length) and the GLC (greatest length from caput femoris) values increased gradually from the first to the fourth group, and these values were higher in the males than the females. Phosphorus and calcium values were higher in the males in adult groups (third and fourth) compared to that for the females; however, they were higher in the females in groups up to adulthood (first and second). While the Ca/P ratio reached the highest value in the second group in the male, it decreased gradually afterwards. In females, the rate, which was close to each other in the first three groups, increased in the fourth group. Surface area size in the female and the male rats was the highest in the second group. In conclusion, changes in the rat bone structure during the development and adulthood periods of the body were revealed, and it was determined that the gender factor was effective in these changes.
Keywords: BET; femur; morphometry; rat; XRF